Effect of a new plant-based high-energy oral nutritional supplement in adult malnourished patients: an open-label, randomized clinical trial - Iglesias Hernández, Natalia Covadonga; Ramos Carrasco, Araceli; De Luis Román, Daniel Antonio; de Pablos-Velasco, Pedro Luis; Calañas Continente, Alfonso; Rodríguez Soto, Miren Josune; López-Gómez, Juan José; Comi-Díaz, Cristina; García-Rey, Silvia; Pérez-Rambla, Clara; García-Luna, Pedro Pablo (Frontiers in Nutrition, 2025)
Background and aimsThe recent global trend toward reducing the consumption of animal-derived products has contributed to a growing demand for plant-based oral nutritional supplement (pbONS) options. PbONS, in addition to achieving good compliance, have an improvement in nutritional status (increased energy and protein intake, body weight, and BMI) on malnourished patients. However, there is no evidence of their impact compared to animal-based ONS (aONS).MethodsA multicenter, open-label, and non-inferiority trial (NCT06055543) was conducted in 5 tertiary hospitals in Spain. Adult malnourished outpatients requiring high-energy ONS for at least 12 weeks (1.5 kcal/ml;200 ml, 2 bottles/day), having signed informed consent, were recruited and randomly assigned (1:1) to receive pbONS or aONS. Randomization was performed using a pre-generated list embedded in the electronic data entry platform. The total number of participants randomized was 149, 75 patients in aONS group and 74 in pONS group. Baseline and final characteristics of the two groups were described and compared in terms of sociodemographic, clinical, compliance, and satisfaction variables.ResultsA total of 129 patients who received pbONS (66) or aONS (74) were included. Weight increased significantly from 55.1 ± 12.7 kg to 57.4 ± 13.1 kg (p-value < 0.001) in the aONS group, and from 55.0 ± 10.7 kg to 57.1 ± 10.7 kg (p-value < 0.001) in the pbONS group, with no significant differences between groups (p = 0.659). It was further confirmed that pbONS is not inferior to aONS in terms of body weight gain. According to GLIM criteria, patients improved their nutritional status 92.1% (58/63) in the aONS group and 95.5% (63/66) in the pbONS group with no statistical difference between groups (p-value = 0.425). Functional strength was increased after 12 weeks: 55.6% (35/63) in aONS and 60.6% (40/66) in pbONS, with no significant difference between groups (p-value = 0.346). Gastrointestinal Symptom Rating Scale (GSRS) scores were lower in both groups at 12 weeks, indicating a reduction in symptom severity.ConclusionPbONS are as effective and well-tolerated as traditional ONS in improving nutritional outcomes, with high patient satisfaction in malnourished patients. This study provides valuable evidence for integrating pbONS into routine clinical practice for the tailored management of patients.Clinical trial registrationThe study was registered on September 21, 2024, with the identifier number NCT06055543.